Study of Ground Movement in a Mining Area with Geological Faults Using FDM Analysis and a Stacking InSAR Method - Qin, Zhengyuan; Agarwal, Vivek; Gee, David; Marsh, Stuart; Grebby, Stephen; Chen, Yong; Meng, Ningkang (Frontiers in Environmental Science, 2021)
Underground coal mining activities and ground movement are directly correlated, and coal mining-induced ground movement can cause damage to property and resources, thus its monitoring is essential for the safety and economics of a city. Fangezhuang coal mine is one of the largest coalfields in operation in Tangshan, China. The enormous amount of coal extraction has resulted in significant ground movement over the years. These phenomena have produced severe damages to the local infrastructure. This paper uses the finite difference method (FDM) 3D model and the stacking interferometric synthetic aperture radar (InSAR) method to monitor the ground movement in Fangezhuang coal field in 2016. The FDM 3D model used calibrated Fangezhuang geological parameters, and InSAR used C-band Sentinel-1A, ascending, interferometric wide (IW) data for 2016. The results show that the most prominent subsidence signal occurs in mining panel 2553N and the area between panel 2553N and fault F0 with a subsidence value up to 57 cm. The subsidence results of FDM 3D model and stacking InSAR to monitor land deformation under the influence of fault are in close agreement, and were verified using two-sample t-test. It was observed that the maximum subsidence point shifted towards the Fault location, from the centre of the mining panel. The tectonic fault F0 is reactivated induced by coal mining and control the spatial extent of the observed ground movement. The impact of dominant geological faults on local subsidence boundaries is investigated in details. It is concluded that ground movement in the study area was mainly induced due to mining activities, with its spatial pattern being controlled by geological faults. These results highlights that the two methods mutually varies their ability to measure mining induced ground movement in the fault dominated areas. The study will improve the understanding of subsidence control, and aid in developing preventive measures in Fangezhuang coalfield with fault reactivation.